Freeze-Drying Technique for Microencapsulation of Elsholtzia ciliata Ethanolic Extract Using Different Coating Materials - Lauryna Pudziuvelyte; Mindaugas Marksa; Katarzyna Sosnowska; Katarzyna Winnicka; Ramune Morkuniene; Jurga Bernatoniene (Molecules, 2020)
The present study reports on the encapsulation of Elsholtzia ciliata ethanolic extract by freeze-drying method using skim milk, sodium caseinate, gum Arabic, maltodextrin, beta-maltodextrin, and resistant-maltodextrin alone or in mixtures of two or four encapsulants. The encapsulation ability of the final mixtures was evaluated based on their microencapsulating efficiency (EE) of total phenolic compounds (TPC) and the physicochemical properties of freeze-dried powders. Results showed that the freeze-dried powders produced using two encapsulants have a lower moisture content, but higher solubility, Carr index, and Hausner ratio than freeze-dried powders produced using only one encapsulant in the formulation. The microencapsulating efficiency of TPC also varied depending on encapsulants used. The lowest EE% of TPC was determined with maltodextrin (21.17%), and the highest with sodium caseinate (83.02%). Scanning electron microscopy revealed that freeze-drying resulted in the formation of different size, irregular shape glassy particles. This study demonstrated good mucoadhesive properties of freeze-dried powders, which could be incorporated in buccal or oral delivery dosage forms. In conclusion, the microencapsulation of E. ciliata ethanolic extract by freeze-drying is an effective method to produce new value-added pharmaceutical or food formulations with polyphenols.